Research progress of KPI anomaly detection in intelligent operation and maintenance - Su WANG; Hua LU; Shuo WANG; Lei CAI; Tao HUANG (Dianxin kexue)
Existing network monitoring and fault repair mostly rely on rule systems or manual processing.However, the increase in network scale and the diversification of services make this approach difficult to deal with.With the rapid development of technology such as machine learning and deep learning, intelligent operation and maintenance theory has also made great progress, using artificial intelligence technology to enhance the intelligent ability of network operation and maintenance.KPI (key performance indicator) anomaly detection is an underlying core technology of intelligent operation and maintenance.A survey on the KPI anomaly detection technology was given.Firstly, the KPI data and KPI anomalies were described.Then the research progress of single-dimensional KPI and multi-dimensional KPI anomaly detection were introduced.Then, the deployment and application problems of KPI anomaly detection were analyzed.Finally, future research directions were discussed.